Perceived competence in disaster preparedness and response among military nurses - Bajarin, Venus (Manila: College of Nursing, University of the Philippines Manila, 2015)
Nurses play an important role in disasters. They are often the first medical personnel on site immediate disaster aftermath. Nurses take the roles as first responder, direct care provider, on-site coordinator of care, information provider or educator, mental health counselor and triage officer (ICN 2009). Hence, the need to have the necessary qualifications to adequately respond to disaster events. To date, limited studies determine the readiness of nurses to respond to disaster events which prompted to researcher to determine the perceived competence of military nurses in disaster preparedness and response at selected military treatment facilities in Metro Manila. It also explored factors that significantly influenced their perceived competence. -- The study utilized a descriptive- correlational design. It was conducted at selected Military Treatment Facilities (MTF) in the Armed Forces of the Philippine in Metro Manila. Emergency Preparedness Information Questionnaire (EPIQ) was utilized to measure the perceived competence in disaster preparedness and response among (n=119) military nurses. -- A total of 137 survey questionnaires were distributed to the qualified samples. However, only 126 out of 137 were returned and 119 only had been considered and included, thus, achieving a response rate of 95.9%. -- Majority of the respondents belongs to age group 25-30 years old (56.30%) with the rank of 1st Lieutenant (31.9%) and 2nd Lieutenant, (26.1%), and with a length of services as military nurses between 6-10 years (40.33%). It also presents that majority of the respondents (60.5%) are general duty nurses and those with other field of specialization such as pediatric, obstetric renal and orthopedic nurses. Most of the military respondents claimed that they were deployed in disaster areas, (63%) and have trainings in disaster management. (79.8%). It is also noteworthy to know that military nurses are very willing and motivated to assume the risk of involvement in disaster, very willing to participate in disaster preparedness activities and want to be involved in their unit's disaster preparedness planning. (M= 4.77, SD- 0.37). However, health care climate (socio-environmental factors) based on the respondent's perception, revealed a somewhat adequate (M=2.79, SD- 0.72) in unit's preparedness and support and their individual preparedness. -- Emergency Preparedness Information Questionnaire (EPIQ) was utilized to determine the perceived competence of the military respondents. Study findings revealed an average level of perceived competence in most of the dimensions measured. (M= 2.50- 3.49). However, the study revealed that on the dimensions of Epidemiology and Surveillance and Isolation (M=2.81, SD- 0.85) and Decontamination and Quarantine (M= 3.09, SD- 0.86), the perceived competence of the respondents are low. It also revealed that all the identified variables (Individual differences, Self-regulation and Health care climate) have a significant relationship with the perceived competence in disaster preparedness. Though, the military rank self-regulations and healthcare climate were found out to be the significant predictors of the perceived competence of military nurses in disaster preparedness and response. -- The study findings conclude that the self-efficacy of military nurses in disaster preparedness and response revealed a competent level in the dimensions such as Ethical Issues in triage, Communication and connectivity and psychology and mental health issues in vulnerable populations. These findings could be best explained by the military respondents who perceived their self-regulations or their motivation or willingness to participate in disaster preparedness as high willingness. -- Based on the above findings, Institutionalization of a disaster management specialization course may be considered. The integration of related trainings that will enhance leadership capabilities in managing disaster response events is highly recommended in order to empower military nurses in disaster planning and policy formulation in disaster management. -- It is further recommended that provision of effective trainings to military nurses which is a crucial steps in designing a well- written emergency preparedness training program on the isolation, decontamination and quarantine procedures specifically to bioterrorism disaster caused by chemical, biological, radiological, nuclear and explosives and pandemic disease outbreak. -- An important initiatives that this study would recommend is to revisit policies regarding the role of military nurses in disaster preparedness and response, and come up with a defined core competencies for the military nurses in their deployment role and in disaster management.
Thesis (Master of Arts in Nursing) -- University of the Philippines Manila, June 2015.
Bibliographical references: leaves 129-135.
Keywords: Military nursing -- Emergency management